Peran Pendidikan Kewarganegaraan dalam Membangun Karakter Bangsa di TK Nusa Indah Bedingin Sugio Lamongan - Alfrianti Alfrianti; Abi Yazid Busthomi; Dhetty Eko; Lailatul Rohmah; Siti Aisyah; Miftahuniz Miftahuniz; Suyono Suyono; Masullah Aprilia; Intan Duwi; Aris Ispriyanti; Agung Sundoro (Pusat Riset dan Inovasi Nasional, 2024)
Civic education has a crucial role in shaping children's character as part of nation building. This study aims to describe how civic education is applied in Nusa Indah Bedingin Sugio Lamongan Kindergarten and its impact on the formation of children's character. The research method used was participatory observation and interviews with teachers and school staff. The results of the study show that civic education in kindergarten is not only limited to the formal curriculum, but also integrated in daily activities and examples given by teachers. Children are taught to appreciate moral values, understand the government system, and actively participate in the life of the nation. The implication of this study is the importance of civic education as a foundation for the formation of a responsible and caring national character for its social environment.